2014
DOI: 10.1007/s00234-014-1414-3
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional shape analysis of the M1 segment of the middle cerebral artery using MRA at 3T

Abstract: The three-view method is convenient for describing the 3D morphology, including the shape information, of the M1 segment. It is a potential method for planning and predicting risk in neurosurgery/neurointervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…We found that, unlike ischaemic stroke, atherosclerotic plaque and stenosis at M1 segment were rare, which is consistent with the findings of an autopsy Open access study. 9 As with healthy population, 28 curved MCAs were more prevalent than their straight counterparts. The dorsal and superior-oriented M1 segment curves were found to be the most common shape of MCAs in our study.…”
Section: Discussionmentioning
confidence: 92%
“…We found that, unlike ischaemic stroke, atherosclerotic plaque and stenosis at M1 segment were rare, which is consistent with the findings of an autopsy Open access study. 9 As with healthy population, 28 curved MCAs were more prevalent than their straight counterparts. The dorsal and superior-oriented M1 segment curves were found to be the most common shape of MCAs in our study.…”
Section: Discussionmentioning
confidence: 92%
“…On the left trans‐temporal B‐mode study, we disclosed an abnormal hyperechogenic signal hampering to identify the lesser wing of the sphenoid, which is the classical anatomical landmark for the M1 segment of the MCA (also known as “sphenoidal or horizontal segment”) (Figure ). Nevertheless, the left M1 segment was clearly highlighted by color‐coded Doppler imaging, appearing unusually thin and crescent‐shaped with posterior convexity, and exhibiting significant flow acceleration (Figure ). Such morphologic and hemodynamic characteristics suggested external compression rather than atherosclerotic stenosis, which appears rarely tubular …”
Section: Discussionmentioning
confidence: 99%
“…According to the vessel projections on the MIP images of the 3D TOF MRA, the shape of the M1 segment was classified into 3 groups according to a previous study ( 23 ): (I) straight; (II) C-shaped; and (III) S-shaped MCA. In order to reduce the influence due to morphological differences of the other 2 types of arteries, only the C-shaped MCA, called the curved MCA, was included and analyzed in this study.…”
Section: Methodsmentioning
confidence: 99%